Exploring SLEEPINESS through home monitoring with ultra-long-term subcutaneous EEG and ecological momentary assessment in sleepy treatment naïve obstructive sleep apnea patients starting CPAP treatment—A study protocol article - Sarkez-Knudsen, Mathias; Ballegaard, Martin; Piilgaard, Henning; Ahrens, Esben; Hemmsen, Martin Christian; Andersen, Tobias Søren; Bradram, Jakob Eyvind; Homøe, Preben (Frontiers in Sleep, 2025)
IntroductionExcessive daytime sleepiness (EDS) is a key symptom for patients with obstructive sleep apnea (OSA). Despite important limitations in the longitudinal monitoring of EDS, the Epworth Sleepiness Scale (ESS), the Maintenance of Wakefulness Test, and the Multiple Sleep Latency Test (MSLT) are the best available objective tests to predict EDS. Limited information exists on the day-to-day fluctuations of sleepiness symptoms from the everyday life perspective of OSA patients. The most feared is sudden sleep episodes that cause traffic accidents. The following study protocol investigates the novel possibilities of ultra-long-term Electroencephalography (EEG) (ULT-EEG) home monitoring in sleepy OSA patients with a subcutaneous implant. We hypothesize that the high-frequency testing from ULT-EEG, in combination with an ecological momentary assessment (EMA), can provide the information to develop new electrophysiological monitoring of sleep propensity as an alternative to the well-established, yet subjective, ESS.MethodsThis clinical exploratory and experimental study will include 15 treatment-naïve patients with severe OSA, with a baseline ESS score above 10. The subjects will be implanted with a two-channel subcutaneous EEG monitoring device upon inclusion and a confirmative polysomnography MSLT. Subcutaneous EEG is recorded 24/7 for 6 weeks before and 6 weeks during continuous positive airway pressure (CPAP) treatment. Daily assessments with the Karolinska Sleepiness Scale, the Psychomotor Vigilance Task test, and a sleep/nap diary will be collected using EMA methods.DiscussionThis study combines data collection from sleepy OSA patients' natural environments using ULT-EEG and EMA methods to obtain sleepiness metrics suitable for developing and preliminarily validating the possibilities of ULT-EEG sleepiness monitoring. We aim to prove a new concept of monitoring sleepiness symptoms in OSA patients and gain new insights into CPAP-related sleepiness rehabilitation.Ethics and disseminationAll participants will provide written informed consent to participate in this study. Ethical approval from the Region Zealand Ethics Committee on 13/09/2021 (SJ939, EMN-2021-06803). The study will be conducted in accordance with local legislation and institutional requirements and comply with the Declaration of Helsinki and the General Data Protection Regulation (GDPR).